Analisa Kerusakan Sistem Electrical Pada Mesin CNC Plasma Cutting Di PT Kenertec Power System - Fikri Ardiyansah; Desmira Desmira (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In the 4.0 era, the machines in the company are very sophisticated, for example, CNC Plasma Cutting machines that use an automatic system run using a computer that is sufficiently given a command. Because of that, maintenance and repair will require a large fee if we can see the level of availability, it is likely to overcome future problems. The method used in this research is a literature study or literature study in scientific journals. The availability of the machine affects the production process, if it does not reach 90% then the machine is not well prevented, this effect affects the damage to the machine, if it is below that means the machine is often damaged. additional personnel and training on the equipment team, especially experts in the field of programming, because then the company does not need to contact the dutch directly to fix problems in the program. Periodic preventive maintenance is carried out to prevent damage to a machine.